2019
DOI: 10.3390/math7090782
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of an Authentication Scheme Using an Identity Based Generalized Signcryption

Abstract: Secure data transmission is a challenging issue in modern data communication. ID based generalized signcryption is a cost effective security primitive which provides authentication or confidentiality, or jointly confidentiality and authentication. Wei's proposed an ID based generalized signcryption scheme for authentication and confidentiality of big data in a standard model, claiming that their scheme holds the security of indistinguishability against adaptive chosen-ciphertext attacks and existential unforge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Shen et al in 2017 [23] improve the security of existing IBGS schemes which is suitable for low storage devices. Waheed et al in 2019 [24] proved that the security of the Wei et al [21] scheme is susceptible to attack and insecure. In the proposed cryptanalysis, the authors launched a security attack on the Wei et al [21] scheme and found that the master secret key of the proposed scheme can be easily compromised.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al in 2017 [23] improve the security of existing IBGS schemes which is suitable for low storage devices. Waheed et al in 2019 [24] proved that the security of the Wei et al [21] scheme is susceptible to attack and insecure. In the proposed cryptanalysis, the authors launched a security attack on the Wei et al [21] scheme and found that the master secret key of the proposed scheme can be easily compromised.…”
Section: Related Workmentioning
confidence: 99%
“…However, the schemes [18][19][20][21][22][23] suffer from a heavy pairing operation due to the use of bilinear pairing. In [24], the authors did not provide any sort of solution to the proposed claims.…”
Section: Related Workmentioning
confidence: 99%
“…In the scheme [29], the authors proposed an ID-based generalized signcryption technique to achieve the security properties of data confidentiality and authentication in the big data environment and claimed that the security of their scheme is formally proved in the standard model. In scheme [30] proposed the updated version of [29], and he claimed that the scheme [29] is not secure in the standard model and does not satisfy (IND-CCA) and (EUF-CMA) properties. Moreover, the third-party PKG is still compromised, and the attacker can easily modify the data in the big data environment.…”
Section: Related Workmentioning
confidence: 99%
“…In References 12 and 13 proposed a cross-domain authentication scheme to solve the security problem that communication signaling will be blocked when most of vehicle devices access the LTE-A network at the same time and perform complete identity verification and key agreement processing for each device. ID-based generalized signcryption is a cost-effective security primitive that provides identity verification or confidentiality, or joint confidentiality and identity verification, 27,28 this scheme is indistinguishable from adaptive selection ciphertext attacks, and has no unforgeability against adaptive selection message attacks. The concept of a smart city based on the IoT is constantly evolving to improve the quality of life of citizens through the practice of information and communication technologies.…”
Section: Related Workmentioning
confidence: 99%